Bystander behavior in school bullying and multidimensional belief in a just world - Mizuno, Kumpei (Frontiers in Education, 2025)
IntroductionBullying is a significant issue that harms children’s health and infringes on their right to education. Understanding the mechanisms of bullying, preventing it, and implementing appropriate interventions are essential for education. Notably, not only the victims and perpetrators but also the bystanders around them play important roles in bullying situations. This study examined the relationship between bullying bystanders’ multidimensional just-world beliefs and their attitudes and behaviors when witnessing bullying.MethodsA vignette-based online survey was conducted with 400 Japanese middle school students (Mage = 13.2, SD = 0.91). The questionnaire required the students to respond independently.ResultsThe analysis showed that intrinsic just-world beliefs were associated with positive attitudes and behaviors toward bullying victims, whereas ultimate just-world beliefs were not. It was found that higher ultimate just-world beliefs were not only related to stronger intentions to mediate bullying but also, to a greater tendency, to blame the victim and a lower likelihood of recognizing bullying in cases where it was witnessed multiple times.DiscussionsMultidimensional just-world beliefs predicted both pro-bullying and anti-bullying attitudes. The findings add substantially to our understanding of the relationship between just-world beliefs and bystanders’ behavior and attitudes, providing novel insights into the understanding of bullying behavior.